The relationship of physical balance in the utilization of pelleted and non-pelleted rations for lambs. - Bell, T.D.; Richardson, D.; Cox, R.F.; Needham, J.W.; John, R. (Kansas Agricultural Experiment Station, 2011)
This project was designed to study the difference between pelleted and non-pelleted rations of different concentrations. Many commercial lamb feeders are pelleting the entire ration and believe it is superior to the same ration hand-fed. At the present time, the extra cost of pelleting varies from $8-$12 per ton. This test and others are designed to determine whether there is enough additional gain in weight and feed efficiency to warrant the use of pelleted rations, and to determine the most desirable ratio of roughage to concentrate.
Keywords: Sheep; Pelleted rations; Non-pelleted rations; Gain; Feed efficiency